(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the philosophical views of Abu Hafs Umar Suhrawardi, one of the major representatives of the teachings of mysticism and Eastern philosophy, the founder of the Ssuhrawardiyya tariqat, on the understanding of the human ego it was analyzed on the basis of the work” Avoriful-maorif " (enlightenment gifts). Also, the work covers the role of the sufis scholar’s ideas about the description of nafs, about the education of nafs in the upbringing of the younger generation.